Breaking the tongue : language, education, and power in Soviet Ukraine, 1923-1934 - Pauly, Matthew D., 1971- (University of Toronto Press, 2014)
Breaking the Tongue examines the implementation of the Ukrainization of schools and children's organizations in the 1920s and early 1930s.